Ketaksamaan Operator Integral Fraksional yang Diperumum pada Ruang Morrey Tak Homogen yang Diperumum - Azizah, Siti Rohmah; Rahman, Hairur; Nasichuddin, Achmad (Jurnal Riset Mahasiswa Matematika, 2024)
A Fractional integral operator is one of the operators in mathematical analysis. Fractional integral operator itself maps any real-valued function into the integral form  of the division of the at function. One of the expansion of fractional integral operator is generalized fractional integral operator. Morrey space is an extension of Lebesgue space. Morrey space is the set of all Lebesgue measurable functions, whose norm is finite over Morrey space. In this study, we will discuss the inequalities of the generalized fractional integral operator on a generalized non-homogeneous Morrey space. We proved of this inequality using the Chebyshev inequality and the Holder inequality.